Comprehensive Sexuality Education Activities in the EFL Lesson through Emergency Remote Teaching (ERT) - Accardo, Silvana Paola (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
This article intends to show how contents of Comprehensive Sexuality Education can be included both in primary and secondary level EFL lessons through the use of different educational technological resources and remote teaching proposals. The passing of National Law 26,150 (2006) created a national program on Comprehensive Sexuality Education (CSE) which enforces the inclusion of perspectives, contents and discursive practices around CSE in all areas of the curriculum —EFL included— and at all levels of the educational system. During these times of pandemic and emergency remote teaching, the inclusion of CSE in our lessons continues to be of paramount importance. This article describes some of the initiatives and practices implemented for the inclusion of CSE.